Images of the Human Being Eighth International East-West Symposium of New Testament Scholars, Caraiman Monastery, May 26 to 31, 2019 - Niebuhr, Karl-Wilhelm; Nicklas, Tobias; Pricop, Cosmin (Mohr Siebeck, 2024)
Bilder des Menschen. Achtes Internationales Ost-West-Symposium Neutestamentlicher Wissenschaftler, Caraiman-Kloster, 26. bis 31. Mai 2019.
PublicationDate: 20241030
Keywords: Hermeneutics -- Pauline Studies -- Biblical anthropology -- Orthodox biblical scholarship -- Bibeldidaktik -- Pauline studies -- Neues Testament -- Kirchengeschichte -- Systematische Theologie -- Array